1988
DOI: 10.1007/bf00154735
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stereoacuity: A comparison of electrophysiological and psychophysical responses in normal and stereoblind observers

Abstract: We compared stereoscopic thresholds determined psychophysically and by using visually evoked potentials in normal adult and stereoblind subjects. For normal observers there was a strong linear relationship between visual evoked potential amplitude and disparity (r = 0.86 on average). However, stereoblind observers' responses showed no relationship to disparity (r = 0.18 on average). For normal observers, log visual evoked potential stereo thresholds determined by an extrapolation procedure were on average with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…These researchers, too, found a negative and a positive peak within time windows of 200-400 ms and 400-600 ms, respectively. The negative peak within 200-400 ms reported in most of the studies (Regan and Beverley 1973;Fenelon et al 1986;Chao et al 1988;Manning et al 1992;Janssen et al 1999) turned out to be the most prominent peak in our study, too. It seems that this is the basic wave in response to disparate stimuli.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…These researchers, too, found a negative and a positive peak within time windows of 200-400 ms and 400-600 ms, respectively. The negative peak within 200-400 ms reported in most of the studies (Regan and Beverley 1973;Fenelon et al 1986;Chao et al 1988;Manning et al 1992;Janssen et al 1999) turned out to be the most prominent peak in our study, too. It seems that this is the basic wave in response to disparate stimuli.…”
Section: Discussionsupporting
confidence: 55%
“…In the literature, results show differences in the latencies and in the number of the peaks recorded. The results reported consist of studies that obtained monophasic (Regan and Spekreijse 1970;Julesz et al 1980;Julesz and Kropfl 1982;Oguchi and Mashima 1989), biphasic (Regan and Beverley 1973;Fukai 1985;Fenelon et al 1986;Skrandies 1987;Chao et al 1988;Manning et al 1992;Janssen et al 1999) and triphasic (Mol and Caberg 1977;Herpers et al 1981;Yanashima et al 1987) waveforms. Besides the results in which the peaks are localized within a 100-200 ms interval (Regan and Spekreijse 1970;Fukai 1985;Skrandies 1987;Yanashima et al 1987;Oguchi and Mashima 1989), there are also results that consist of peaks within a wide 100-600 ms window (Mol and Caberg 1977).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…As for stereoscopic 3D stimuli, Sahinoğlu [12] reported that the amplitude of the N300 component within intervals of 200-400 msec from the left and right occipital cortices increased in response to the depth of convergent disparities. The role of N300 in the occipital area is known to be related to disparate stimuli [26][27][28][29][30]. Our differently shaped stimuli were also convergent (negative) disparities.…”
Section: Discussionmentioning
confidence: 97%